On the question of studyng dust-like formations in urban ecosystems - D. T. Ukarkhanova; D. V. Moskovchenko; A. A. Yurtaev (Бюллетень Почвенного института им. В.В. Докучаева, 2020)
According to the World Health Organization, more than 80% of urban residents are at risk due to unsatisfactory air quality and air pollution, which causes approximately 4.2 million deaths per year. The purpose of the work is to give an overview of scientific articles related to the dustiness of the city’s natural environments. The articles of foreign and Russian researchers were analyzed - the definition of urban road dust was given; the primary technogenic and natural sources of dust particle generation in the city, thephysical and chemical properties of road dust, their dependence on climate, the type of roads and city architecture, the effect of photolysis on physicalchemical characteristics of dust particles are reviewed as well. Particular attention is paid to the negative impact of dust particles PM2.5 and PM10 on human health and the environment. The question of the absence in Russian scientific practice an officially recognized methodology for the settled dust sampling with updating the regulatory documentation on the methodology for the sampling of fine particles suspended in the air is considered. Recommendations are given on the creation of the regulatory framework governing the sampling and analysis of road dust, which is confirmed by the numerous conclusions of both foreign and some domestic researchers as an environmental geo-indicator.